Bill 86 Tramples on Minority Rights and Should be Scrapped - Quebec Community Groups Network (QCGN) (2016)

Brief to the Committee on Culture and Education : Quebec and the Minority Language Educational Rights and Canada’s English Linguistic Minority Communities: A New Partnership - Quebec Community Groups Network (QCGN) (2016)
Voting in elections is an intrinsic right for all Quebecers. It is beyond democratic tradition for government to capriciously remove these rights without a pressing and substantial reason. Quebec’s English public school system is a key institution of the English-speaking community of Quebec, a linguistic minority community. The management and control of these institutions is a matter of governance subject to minority language educational rights contained in the Canadian Charter of Rights and Freedoms, and Quebec’s democratic tradition, expressed in the political rights guaranteed by the Quebec Charter of Human Rights and Freedoms.
Keywords: Official Language Minority Community (OLMC)

Mémoire à la Commission de la culture et de l’éducation : Le Québec et les droits à l’instruction dans la langue de la minorité, et les communautés d’expression anglaise en situation minoritaire au Canada : Un nouveau partenariat - Quebec Community Groups Network (QCGN) (2016)
Voter aux élections est un droit intrinsèque pour tous les Québécois. Mais le gouvernement va à l’encontre de sa tradition démocratique en révoquant capricieusement ce droit sans aucune raison impérieuse ou importante. Le système d’écoles publiques anglophones du Québec est une institution qui joue un rôle clé au sein de la communauté d’expression anglaise de la province — une communauté linguistique en situation minoritaire. La gestion et le contrôle de ces institutions sont une question de gouvernance qui touche les droits à l’instruction dans la langue de la minorité, ces droits étant enchâssés dans la Charte canadienne des droits et libertés et dans la tradition démocratique du Québec, ainsi qu’exprimés dans les droits politiques garantis par la Charte des droits et libertés de la personne du Québec. Le gouvernement du Québec a le devoir de reconnaître sa communauté linguistique minoritaire et de travailler en partenariat avec elle afin de garantir la gestion et le contrôle efficaces du système d’écoles publiques anglophones.
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)
Number of pages: 24